Standard physical designs of land management technologies and determinants of household adoption intentions in Goyrie watershed, southern Ethiopia - Dessalegne Chanie Haile; Yechale Kebede Bizuneh; Mulugeta Debele Bedhane; Abren Gelaw Mekonnen (Environmental Challenges)
The adoption of land management technology (LMT) is crucial for minimizing soil erosion and increasing agricultural productivity, both of which are essential components of sustainable development. Therefore, different LMTs have been adopted in the Goyrie Watershed of southern Ethiopia. However, the technical designs of the adopted technologies have not yet been assessed. Thus, the objective of this study is to evaluate the technical designs of adopted LMTs in relation to standards as well as to identify the factors that influence households' intentions to adopt LMT dimensions in the suggested standards. Data were collected through field measurements, observations, focus group discussions, key informant interviews, and 291 randomly selected heads of household. Data were analyzed using frequency, mean, standard deviation, and structural equation modeling (SEM). This study found that 30 % of the technical aspects of the adopted LMTs on private farmlands and 12 % on communal lands met the recommended national standards. However, field measurements found that 70 % of private farmlands and 88 % of communal lands in the adopted LMT technical designs failed to fulfill the required national standards. This problem was more pronounced on communal land. The SEM estimation revealed that households’ assumptions about development agents and households’ perceptions of the benefits of LMTs were found to significantly and positively influence the probability of households’ intentions to adopt LMTs in line with the referenced standards. Whereas households trust village memberships, the nature of soil types and training opportunities significantly but negatively predicted the probability of households’ intention to adopt LMTs in relation to standards. The study suggests that national and regional governments provide adequate training opportunities for farmers on how to design and implement LMT dimensions in accordance with recommended standards.